PENGEMBANGAN VIDEO PEMBELAJARAN BERBASIS TPACK DALAM MATERI PECAHAN UNTUK SISWA KELAS IV SD - Rebica Afsari; Nila Kesumawati; Nora Surmilasari (Universitas Negeri Medan, 2021)
This study aims to develop TPACK-based learning videos in fraction material for fourth grade elementary school students that are valid, practical and have a potential effect on student learning outcomes. This research is research and development using the ADDIE model with five stages, namely analysis, design, development, implementation, and evaluation. The research took place at SDN 79 Prabumulih. The research subjects were 20 fourth grade elementary school students. Data collection was carried out by means of a media expert validation questionnaire, material expert, student response questionnaire, and student test questions. The data are analyzed quantitatively and qualitatively. The validation results of the validators got an average validation score of 95.43% with a very valid category. The results of student responses based on small group trials got an average score of 94.87% with a very practical category. The results of the large group trial get an average of 88.25% in the very good category or have a potential effect on student learning outcomes. It can be concluded based on the results of data analysis of TPACK-based learning videos in fraction material for fourth grade elementary school students including learning videos that are valid, practical, and have a potential effect on learning outcomes. Overall, TPACK-based learning videos in fraction material for fourth grade elementary school students have been suitable for use in learningKeywords : Development Of Learning Videos, TPACK, Fractions